Financial Ratio Analysis to Measure Financial Performance at PT Astra International, Tbk - Titik Purwaningtyas; Enggun Gunawan; Mahardika Sugiawan (International Publisher, 2023)
In general, the purpose of establishing a company is to obtain optimal profits or profits according to the company's capabilities. Earning a profit for the company is an effort to maintain business continuity and increase the expected growth. To find out the success of a company in achieving these goals, financial measures or indicators are needed. Financial statement analysis needs to be done by every company so that management can find out the company's performance in that year. The main purpose of this research is to determine the financial position, calculation and interpretation of the company's financial ratios. The method used in this research is descriptive quantitative, namely the method used to describe, explain, summarize various conditions, situations, or various research variables. The ratio analysis used in this research is the liquidity ratio, solvency ratio and profitability ratio. The results show that the company is declared liquid but has not been able to take advantage of existing assets and equity to get maximum revenue.